The Use of a Virtual Patient to Follow Pleural Pressure Changes Associated with Therapeutic Thoracentesis. Issue 12 (December 2017) - Gólczewski, Tomasz; Stecka, Anna M.; Michnikowski, Marcin; Grabczak, Elżbieta M.; Korczyński, Piotr; Krenke, Rafał
Purpose: Influence of therapeutic thoracentesis on the pleural pressure (Pp) has been discussed in many clinical studies, however reasons of Pp changes are not precisely established. The aim of the study was to use a previously elaborated virtual cardiopulmonary patient (VP) in analysis of impact of physiological factors on Pp during the procedure. Methods: Simulations were performed on VP with default values of parameters for which VP simulated the respiratory system of the average 50-year-old healthy Polish woman according to spirometric examination. Alterations of Pp and the amplitude of Pp changes related to breathing (AP) were analyzed. Model parameters related to chosen factors were deviated from their default values to analyze the degree of their impact on Pp and AP. The analysis was based on and supported by our own clinical data. Results: The Pp and AP alteration intensity appeared to be most sensitive to the compliances of the rib cage and mediastinum, and the nonlinearity of the dependence between the recoil pressure and the lung volume: the lower the compliances and the higher the nonlinearity were, the deeper the Pp fall during the procedure and the bigger the AP increase were observed. Conclusions: Experiments in silico are very useful in analyzing sophisticated physiological and medical problems. They made it possible to show which factors are particularly responsible for changes in Pp during thoracentesis. In the future, they may be useful in establishing objective conditions under which thoracentesis needs to be stopped.